1999
DOI: 10.1021/jp990116l
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of Zn, Ga, and Fe into HZSM-5 Cavities by Sublimation:  Identification of Acid Sites

Abstract: M/ZSM-5 zeolites with M = Ga, Fe, or Zn were prepared by subliming volatile compounds onto HZSM-5. They were characterized by XRD, H2-TPR, CO-TPR, FTIR, adsorption of pyridine and acetonitrile-d 3 and, in the case of Fe/ZSM-5, also by ESR spectroscopy. Immediately after sublimation, the concentration of Brønsted acid sites is low, but with Ga/ZSM-5 and Fe/ZSM-5, it rises again after hydrolysis. This dissipation of multipositive ions to monopositive ions, each located near the negative countercharge in the zeol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
154
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(164 citation statements)
references
References 57 publications
10
154
0
Order By: Relevance
“…Entropic values include the contributions of the transitional, rotational, vibrational, and electronic partition function for zeolite cluster and for all gaseous species involved in the reaction. 29,57,58 and similar to the so-called "diamond core" structure of the active site in the MMO enzyme. 59 Prins and co-workers 25 have proposed various shell models consisting of different back scattering pairs fitting the EXAFS spectrum of iron sites in ZSM-5 zeolite.…”
Section: Computational Detailsmentioning
confidence: 71%
See 2 more Smart Citations
“…Entropic values include the contributions of the transitional, rotational, vibrational, and electronic partition function for zeolite cluster and for all gaseous species involved in the reaction. 29,57,58 and similar to the so-called "diamond core" structure of the active site in the MMO enzyme. 59 Prins and co-workers 25 have proposed various shell models consisting of different back scattering pairs fitting the EXAFS spectrum of iron sites in ZSM-5 zeolite.…”
Section: Computational Detailsmentioning
confidence: 71%
“…According to numerous experimental studies on the nature of iron sites in Fe-ZSM-5 regarding the zeolite preparation/ activation steps, 25,29,41 it has been concluded that iron first exists as isolated Fe species with tetrahedral coordination, which upon subsequent steaming and calcination are transformed into hydroxylated binuclear complexes. 25,33 In this structure, iron cations are in the oxidation state Fe III and are completely inactive for the N 2 O decomposition.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…5B, in addition to the apparent bands in the range 3350-3200 cm À1 , which were attributed to ammonia coordination on Lewis acid sites, two weak yet clear absorption peaks at 3220 and 3190 cm À1 emerged in the N-H stretching region. 26,28 It was clear that Zn modication not only produced a number of Lewis [14][15][16]30,31 can provide Lewis acid sites in Znmodied ZSM-5 or beta zeolite. Similarly, we speculated that the Lewis acid sites in Zn x /S-1 were also associated with their Zn species.…”
Section: -29mentioning
confidence: 99%
“…The catalytic performance is due to iron in the zeolites [5][6][7][8][9]. Different forms of iron have been identified in the FeZSM-5 zeolites [10][11][12][13][14][15][16]: (1) isolated ions isomorphously substituted in the MFI framework; (2) ions in cation-exchange positions; (3) iron complexes of low nuclearity in extraframework positions; (4) Fe oxide nanoparticles of < 2 nm size in the micropores; and (5) large Fe oxide particles (2-25 nm) located at the external surface of zeolite crystals. However, only a small part of the total iron is usually active in the hydroxylation of benzene [5,7,8].…”
Section: Introductionmentioning
confidence: 99%